Answer:
20/9
Explanation:
Simplify the following:
6 + 2/3 - (4 + 4/9)
Put 4 + 4/9 over the common denominator 9. 4 + 4/9 = (9×4)/9 + 4/9:
6 + 2/3 - (9×4)/9 + 4/9
9×4 = 36:
6 + 2/3 - (36/9 + 4/9)
36/9 + 4/9 = (36 + 4)/9:
6 + 2/3 - (36 + 4)/9
| 1 |
| 3 | 6
+ | | 4
| 4 | 0:
6 + 2/3 - 40/9
Put 6 + 2/3 - 40/9 over the common denominator 9. 6 + 2/3 - 40/9 = (9×6)/9 + (3×2)/9 - 40/9:
(9×6)/9 + (3×2)/9 - 40/9
9×6 = 54:
54/9 + (3×2)/9 - 40/9
3×2 = 6:
54/9 + 6/9 - 40/9
54/9 + 6/9 - 40/9 = (54 + 6 - 40)/9:
(54 + 6 - 40)/9
| 1 |
| 5 | 4
+ | | 6
| 6 | 0:
(60 - 40)/9
| 6 | 0
- | 4 | 0
| 2 | 0:
Answer: 20/9